The narrative of irony and the irony of narrative: Time in Milan Kundera’s novels - Amin, Ramy (AUC Knowledge Fountain, 2018)
The purpose of this thesis is to give a fresh account of the study of irony by investigating the role of time in the reading process. The study follows the idea of temporal displacement within the text to understand and profile the patterns of irony, and provides a formal reading of Milan Kundera's major novels. In this thesis, a systematic method of tracing the movement of irony to arrive at the structure of the text is taken up in terms of The Book of Laughter and Forgetting, The Unbearable Lightness of Being, and Immortality. The thesis showcases three major types of irony in a manner that casts light on the particularities of three different texts. By focusing on the most important literary device used in Kundera's literary fiction, I demonstrate the function of situational, motif and thematic irony, whenever one or any combination of these ironic modes seems appropriate to the reading of the text at hand.